Conflict, war, and peace an introduction to scientific research - Mitchell, Sara McLaughlin; Vasquez, John A. (SAGE, 2014)
Focusing on the factors that shape relationships between countries and that make war or peace more likely, this collection of articles by top scholars explores such key topics as dangerous dyads, alliances, territorial disputes, rivalry, arms races, democratic peace, trade, international organizations, territorial peace, and nuclear weapons. Each article is followed by the editors' commentary: a "Major Contributions" section highlights the article's theoretical advances and relates each study to the broader literature, while a "Methodological Notes" section carefully walks students through the techniques used in the analysis. Methodological topics include research design, percentages, probabilities, odds ratios, statistical significance, levels of analysis, selection bias, logit, duration models, and game theory models.